Leo Strauss and Anglo-American democracy : a conservative critique - Havers, Grant N., 1965- (Northern Illinois University Press, 2013)
"Interprets Leo Strauss's political philosphy from a conservative standpoint and argues that Strauss was a Cold War liberal. Suggests inattention to Christianity is crucial to the Straussian portrayal of Anglo-American democracy as a universal regime whose eternal ideals of liberty and constitutional governmnent accord with the teachings of Plato and Aristotle, rather than the Gospels"--